Experimental and theoretical electron-density study of three isoindole derivatives: topological and Hirshfeld surface analysis of weak intermolecular interactions - Chęcińska, Lilianna; Grabowsky, Simon; Małecka, Magdalena; Rybarczyk-Pirek, Agnieszka J.; Jóźwiak, Andrzej; Paulmann, Carsten; Luger, Peter (Acta crystallographica. Section B, Structural science, 2011)
A combined experimental and theoretical study of three isoindole derivatives was made on the basis of a topological analysis of their electron‐density distributions. Experimental electron densities were determined from high‐resolution X‐ray diffraction data sets measured with synchrotron radiation at 100 K, whereas theoretical calculations were performed using DFT methods at the B3LYP\6‐311++G(3df,3pd) level of approximation. Both experimental and theoretical models are in good agreement with each other. Since the analysed structures possess a variety of hydrogen‐bonding interactions, weak intermolecular contacts of C—H...C(π), C,N(π)...C,N(π) and H...H types were subject to our special interest and are discussed in detail. They were characterized quantitatively and qualitatively by topological properties using Bader's Atoms in Molecules theory and by mapping the electron‐density distribution, electrostatic potential and a geometric function on the Hirshfeld surface. This way the forces and directions of intermolecular interactions as present on the molecular surfaces were depicted and described. These interactions not only guide crystal packing, but are likewise important for recognition processes involving (aza)isoindole fragments in a biological environment.